Law and justice in the courts of classical Athens - Lanni, Adriaan (Cambridge University, 2013)
Adriaan Lanni draws on contemporary legal thinking to present a new model of the legal system of classical Athens. She analyzes the Athenians' preference in most cases for ad hoc, discretionary decision making, as opposed to what moderns would call the rule of law. Lanni argues that the Athenians consciously employed different approaches to legal decision making in different types of courts. The varied approaches to the legal process stem from a deep tension in Athenian practice and thinking, between the demand for flexibility of legal interpretation consistent with the exercise of democratic power by Athenian jurors; and the advantages of consistency and predictability. Lanni presents classical Athens as a case study of a sophisticated legal system with an extraordinarily individualized and discretionary approach to justice.